Applying the indexing system for assessment of effectiveness of the exhaust emission compliance certification process for passenger cars. (26th October 2022) - Pandey, Abhinav; Pandey, Govind; Mishra, Rajeev Kumar
Abstract : The inspection/maintenance programmes exist in most countries, aiming at vehicular emission reduction through exhaust emission monitoring and compliance policy to the extant norms. However, considering the absence of an intra-vehicle approach, the higher success rate of vehicles towards compliance policy remains a grey area. The paper attempts to examine this issue through the application of an exhaust emission index (EEI) for petrol-driven cars. The study observed two different scales finding that the Bharat Stage emission norm scale method reports lower ranges of EEI compared with the linear scale (LS) method (EEImin-BSNS = 1.12 and EEImin-LS = 1.25; EEImax-BSNS = 20.70 and EEImax-LS = 29.54). The LS method and the maximum operator form of aggregation are recommended as these can find the highest number of non-compliant cars (21.81% and 12.03% of the 'poor' class, respectively) in the whole fleet tested. The EEI gives a more scientific approach to vehicular emission evaluation, like what the air quality index does in the case of the ambient air quality. It helps vehicle owners know their car's emission status as a quick reference index (EEI). The accurate status of such emission further helps the policymakers affect the better phasing-out norms.